Design Of Vegetable Logistics Network from Tanah Karo to Medan City - Rizky Pratama; Kristia Ayu Putri Halawa; Anita Christine Sembiring (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Indonesia, as an archipelagic nation, faces significant challenges in establishing an efficient food logistics system, particularly in major agricultural centers such as Karo Regency, North Sumatra. This region is recognized as a key producer of vegetables including cabbage, carrots, and tomatoes, contributing strategically to national food security. However, the distribution system has been hindered by extended supply chains, limited infrastructure, and information asymmetry among supply chain actors. This study was conducted to design an optimal distribution network and to evaluate the efficiency of cost allocation using Linear Programming (Minimum Least Cost Allocation) and Distribution Requirements Planning (DRP) methods. Data were collected through field surveys, interviews, and secondary sources from the Central Bureau of Statistics. The findings indicated that the distribution of cabbage and carrots was relatively efficient, while tomatoes experienced significant supply shortages. DRP analysis for the next four periods projected a positive inventory trend, yet declining stock levels highlighted the need for more accurate demand forecasting. Integration of local food systems into national logistics models and the adoption of digital distribution systems were identified as potential solutions. This study is expected to serve as a reference for developing resilient agricultural logistics policies in other regions. Keywords: Food Logistics, Distribution Network, Linear Programming, Distribution Requirements Planning (DRP), Agricultural Supply Chain, Karo Regency.